2013
DOI: 10.1128/aem.02658-12
|View full text |Cite
|
Sign up to set email alerts
|

Invertase SUC2 Is the Key Hydrolase for Inulin Degradation in Saccharomyces cerevisiae

Abstract: bSpecific Saccharomyces cerevisiae strains were recently found to be capable of efficiently utilizing inulin, but genetic mechanisms of inulin hydrolysis in yeast remain unknown. Here we report functional characteristics of invertase SUC2 from strain JZ1C and demonstrate that SUC2 is the key enzyme responsible for inulin metabolism in S. cerevisiae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 24 publications
(23 reference statements)
1
31
0
Order By: Relevance
“…2). Our previous study observed that disruption of the SUC2 gene in the parental strain of JZH completely inhibited its growth in inulin but it remained slow growth on sucrose (Wang & Li, 2013). This finding indicated that there are additional enzymes possessing low invertase activities in the strain JZH, which results in sucrose utilization and benefits high-content FOS production by the strain.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…2). Our previous study observed that disruption of the SUC2 gene in the parental strain of JZH completely inhibited its growth in inulin but it remained slow growth on sucrose (Wang & Li, 2013). This finding indicated that there are additional enzymes possessing low invertase activities in the strain JZH, which results in sucrose utilization and benefits high-content FOS production by the strain.…”
Section: Resultsmentioning
confidence: 75%
“…The yeast S. cerevisiae can hydrolyze inulin with low DP into fructose and glucose by secretively expression of the invertase SUC2 that has an exo-inulinase activity (Wang & Li, 2013;Li, Fu et al, 2015). To remove the exo-inulinase activity, the SUC2 gene was disrupted in the S. cerevisiae strain JZH generating a strain JZHΔS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 that more monosaccharides (glucose and fructose) were released from inulin by the action of the recombinant inulinase produced by the transformant W14-3-INU-112 than by that of invertase produced by the strain W12d carrying the DNA fragments without the INU1 gene, indicating that the INU1 gene cloned in this study indeed was expressed in the transformant W14-3-INU-112 and inulin hydrolysis was enhanced by the action of the recombinant inulinase produced by the transformant W14-3-INU-112. Indeed, many results have shown that the invertase produced by various strains of S. cerevisiae have low inulinase activity [26,27]. That was why the inulinase gene obtained in this study was expressed in Saccharomyces sp.…”
Section: Discussionmentioning
confidence: 90%
“…However, it has been well documented that K. marxianus cannot tolerate high concentrations of ethanol differently from Saccharomyces cerevisiae that is also a widely used industrial microorganism for its high ethanol production (Lane and Morrissey 2010;Nevoigt 2008;Ostergaard et al 2000). Unfortunately, S. cerevisiae cannot produce high concentrations of ethanol from inulin due to its weak capability of utilizing fructooligosaccharides with a high degree of polymerization Lim et al 2011;Wang and Li 2013). Therefore, it has been confirmed that introduction of a heterologous inulinase gene into S. cerevisiae could improve its inulin utilization and ethanol production.…”
Section: Introductionmentioning
confidence: 98%